Power Consumption in Milling of Titanium Grade-2 under an improved Cutting Fluid Supply System - Darulihshan Bin Abdul Hamid, Louis Denis Kevin Catherine (International Journal of Advanced Science and Technology, 2020)
The machining of titanium is very costly due to the high market price of the material, required cutting tool and power consumption among others. Titanium is among the hardness engineering material and currently, its weight-to-strength ratio makes it one of the most attractive material in many industries such as aerospace, automotive, oil and gas, and medical industries. The requirement in terms of cutting power during the machining of titanium is critical and, in this paper, a study was undertaken on the relationship of three milling parameters namely spindle speed, feed rate and depth of cut. The milling experiment was performed on a DMU 50 3-axis CNC milling machine under a newly developed MQL adjustable supply system. The cutting fluid supply system makes use of two nozzles that were located along and against the feed direction couple with an inclination of 45° towards the tip of the cutting insert. This experiment makes use of the design of experiment (DOE) with 3 factors at 2 levels and three replicates. It was revealed that some milling parameters have a more direct impact on the cutting power compare to others.